Simulation of Betel Leaf Extraction as a Provision of Entrepreneurship Knowledge for Students Regarding the Preparation of Raw Materials for Pharmaceutical Products - Reza Anindita; Dede Dwi Nathalia; Intan Kurnia Putri; Melania Perwitasari; Maya Uzia Beandrade (Universitas Lambung Mangkurat, 2024)
Referring to the need to provide materials and skills regarding the preparation and extraction of natural ingredients with medicinal potential to vocational pharmacy students, it is necessary to carry out integrated school Community Service (Pengabdian Kepada Masyrakat or PKM) activities. This Community Service aims to assess the level of knowledge and skills regarding the preparation and extraction of betel leaf simplicia before being formulated into various pharmaceutical products. This Community Service activity was carried out using the method of simulation and demonstration on the preparation and extraction of green betel leaf simplicia. The results of the activities were then evaluated using the pre and post-test methods to measure participants' understanding of the preparation and extraction of betel leaves. The participants of this Community Service were from Daya Utama Vocational High School, consisting of 26 students accompanied by three supervising teachers. Before being given materials and skills for preparing and extracting natural ingredients, the average score of students' knowledge level was 52.5. After the provision of materials and skills, it increased to 69.3. The conclusion was that the student's knowledge level increased by 16.73, with the t-test results showing a significant difference before and after the provision of materials and skills.